Validity of a nomogram to predict long distance running performance - Coquart, J. B. J.; Alberty, M.; Bosquet, L. (The Journal of Strength and Conditioning Research, 2009)
The purpose was to test the validity of a nomogram to predict performance at distances ranging from the 10 km to the marathon. Official running rankings of the French Athletics Federation for the men's 10 km, 20 km, and marathon were scrutinized from 2002 to 2006. Performances of runners who competed in the 3 distances during the same year were noted (n = 330). Predicted performance by the nomogram was obtained for each distance from the performance at 2 other distances. Actual and predicted performances were compared by a Wilcoxon matched pairs test. The magnitude of the difference was assessed by the effect size (ES). Correlation and Bland-Altman plots were used to evaluate the association and the level of agreement between actual and predicted performances. The nomogram overestimated performance at the 10-km distance (13 seconds; p = 0.03) and underestimated performance at the 20-km distance (27 seconds; p < 0.01). The overestimation for the marathon was not significant (85 seconds; p = 0.06). Whatever the distance, ES were trivial (-0.04 < ES < 0.05). Correlations were 0.89 for the 10 km and the marathon and 0.97 for the 20 km. The limits of agreement represented 10.2, 6.1, and 13.2% of the mean of actual and predicted performances in 10 km, 20 km, and marathon, respectively. These results support the validity of the nomogram to predict performance on 10 km, 20 km, and marathon from the performance at 2 other distances. The accuracy of predictions is better when performance is interpolated. Given their validity and accuracy, interpolated predictions of the nomogram may be used to prescribe realistic training intensities during tempo runs, but also to determine the optimal strategy during the race.